Managing volatile requirements in web applications - Urbieta, Mario Matías; Rossi, Gustavo Héctor; Distante, Damiano; Schwinger, Wieland (2013)
Web applications allow business to offer services or products to numerous users with different culture, context, and needs. There are situations where applications must adapt to unforeseen and temporary business requirements, such as a one- off market campaign to launch a new product, beta features for engaging users, or disaster solidarity features that remain in the application for a period of time. In this paper, we summarize an approach for dealing with this sort of volatile requirements and present challenges in the research field that must be addressed.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
IEEE International Symposium on Web Systems Evolution (15º : 27-27 Sept. 2013 : Eindhoven)
Keywords: APLICACIONES WEB; REQUERIMIENTOS; PROCESOS DE NEGOCIO